BIOKIDS: AN INNOVATION FOR INTEGRATION OF NAQLI AND AQLI KNOWLEDGE - Nur Suriana Mohd Norizan; Mohamed Akhiruddin Ibrahim; Siti Rubaini Mat; Latipah Mohd Noor; Afif Arifin (Journal of Islamic, Social, Economics and Development, 2017)
Biology is a branch of science that deals with living organisms and vital processes.This knowledge such as human creation is mentioned well throughout the Quran. One of themiracles in the Quran is that it describes accurately the embryonic stages during creation andformation of a fetus. Little did the recital knew about embryology, a medical terminology forhuman development in the motherâ€™s womb. Therefore, it is important to relate the science ofBiology and Quran which meets the physical and spiritual needs in order to produce a balancedholistic generation. This concept is known as integration of naqli and aqli that combines therevealed knowledge and modern sciences. Therefore, this study aims to introduce and discussa tool named as â€œBiokidsâ€ courseware that helps the children to understand more on Biologywith the reflection of the integration of naqli and aqli knowledge. This study involved qualitativemethod, which is collecting data obtained by conducting a review of Quranic verses that isrelated to the area of knowledge. This effort is hoped to attract kids to learn more aboutBiology; as the interactive courseware provides new method of learning to people especiallythose at young age who would love to have more active learning environment. Future researchmay also be focused on designing and developing an interactive courseware for Biology subjectin collaboration with Biology teachers and educational professionals.